Pembelajaran Jarak Jauh Pendidikan Pancasila dan Kewarganegaraan Pada Masa Pandemi Covid-19 - Rachman, Fazli; Azam, Quadi (Journal of Moral and Civic Education, 2021)
The COVID-19 pandemic forces governments to close schools and adapting to distance learning. This research article aims to expose the effectivity of distance learning on Pancasila and Civic Education (PPKn) subject for students living in oil palm plantation areas in three villages in North Sumatra. Data was collected by conducting surveys, interviews and documentation study from October to December 2020. Data were analyzed using an interactive model. The result shows that civic education distance learning is ineffective because: (1) the limitation in supporting technology for distance earning and internet access cause limited connectivity with civic education learning resources; (2) civic education distance learning is dominated by task work activities; (3) learning tends to be monotonous because of minimal creativity and innovation; (4) minimal quality of parental assistance because the communication between teachers and parents is not well-established; (5) students find it difficult to understand civic education learning material. The unsatisfactory learning process and outcomes during the distance learning cause 60% of respondents consider civic education distance learning during the COVID-19 pandemic was ineffective. Keywords: Pancasila and Citizenship Education Course, distance learning, students in plantation areas ABSTRAK Pandemi Covid-19 memaksa pemerintah untuk menutup sekolah dan beradaptasi ke pembelajaran jarak jauh. Artikel penelitian ini bertujuan memotret efektivitas pembelajaran jarak jauh (PJJ) pada mata pelajaran PPKn. Penelitian ini dilakukan pada tiga desa di wilayah perkebunan sawit di Sumatera Utara. Data dikumpulkan dengan melakukan survei, wawancara, dan studi dokumentasi selama bulan Oktober hingga Desember 2020. Data dianalisis dengan model interaktif. Penelitian menunjukan PJJ mata pelajaran PPKn tidak efektif pelaksanaannya karena: (1) keterbatasan perangkat teknologi pendukung PJJ dan akses internet menyebabkan keterbatasan keterhubungan dengan sumber belajar PPKn; (2) PJJ PPKn didominasi aktivitas pengerjaan tugas; (3) pembelajaran cenderung monoton, minim kreativitas dan inovasi; (4) kualitas pendampingan orang tua rendah karena komunikasi guru dengan orang tua tidak terjalin; (5) siswa sulit untuk menguasai substansi materi pembelajaran PPKn. Proses pembelajaran dan pencapaian hasil belajar yang tidak maksimal selama PJJ PPKn tersebut menyebabkan lebih dari 60% responden menganggap PPKn Masa Pandemi Covid-19 tidak efektif. Kata kunci: mata pelajaran PPKn, pembelajaran jarak jauh, siswa di perkebunan